A Leak Free Phase Change Materials with Enhanced Thermal Buffering Properties by TiO2/Biochar - Ariyanti, Dessy; Huda, Khoirul; Bayu Samudra, Muhammad; Lesdantina, Dina; Adi Saputra, Erwan; Hamzah, Fazlena (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2023)
A leak free organic phase change material of palmitic acid with enhanced thermal buffering properties was synthesized by simple chemical TiO2/biochar encapsulation process. By utilizing the optimum amount of TiO2 as an encapsulation agent the minimalization of leakage phenomena during the phase change process can be achieved with the value 20-25% of weight loss. Furthermore, the additional sugar cane bagasse-based biochar that was introduced to the encapsulation system acts as a support matrix that enhances further the leakage properties into free leak category with the percentage of weight lost 1.1-1.4 %. Moreover, the introduction of sugar cane bagasse-based biochar in the encapsulation system of the palmitic acid PCM can improve the thermal buffering properties by keeping a package box temperature in the range of 2-80C for more than 20 h by means small increment of temperature 0.72oC/h. Keywords: PCM, encapsulation, palmitic acid, thermal buffering, leakage